Biofortificação agronômica de hortaliças folhosas: cenários atuais e potencialidades - Biafora, Murilo Rabelo (Universidade Federal de São Carlos, 2025)
Hidden hunger, characterized by the deficiency of essential micronutrients in the diet, affects billions of people worldwide, raising the urgent need for effective strategies to mitigate it. This study aimed to evaluate agronomic biofortification of leafy vegetables as a viable solution to enrich foods with minerals such as zinc and iron, addressing both conventional cultivation methods and hydroponic systems. To this end, a literature review of the most relevant publications between 2018 and 2023 was carried out, focusing on research that discusses the increase in the concentration of these micronutrients in vegetables. The results indicate that agronomic biofortification can significantly increase zinc and iron levels in vegetables, offering a less costly and faster alternative compared to genetic biofortification. The discussion highlights the potential of this practice in reducing nutritional deficiencies in Brazil, especially when integrated with hydroponic cultivation systems. It is concluded that the agronomic biofortification of leafy vegetables presents itself as a promising strategy to combat hidden hunger and promote public health, contributing to food security.
Agronomic biofortification of leafy vegetables: current scenarios and potential
Keywords: Biofortificação; Micronutrientes; Hortaliças; Hidroponia; Segurança alimentar; Biofortification; Micronutrients; Vegetables; Hydroponics; Food security; CIENCIAS AGRARIAS